The Effect of Feeding Non-Antioxidant Feed on The Degree of Dysplasia in Formaldehyde-Induced Wistar Rats - Ni Putu Ayu Nindya Dewi Cahya Putri; Anak Agung Ayu Niti Wedayani; Ima Arum Lestarini; Abdul Qadar Punagi; Nova Audrey Luetta Pieter; Muhammad Husni Cangara; Novia Andansari Putri Restuningdyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Nasopharyngeal dysplasia is a condition of abnormal cellular growth that occurs due to the failure of nasopharyngeal epithelial cells in carrying out cellular adaptation. This condition can occur due to the continuous inhalation of toxic compounds, such as formaldehyde, which has genotoxic and cytotoxic effects that can induce cellular damage. One of the compound activity associated with reducing risk of dysplasia is antioxidant activity. Therefore, it is important to know whether the presence of antioxidant activity affects the occurrence of dysplasia. This study is an experimental study with a post-test only control group design which aims to determine the effect of Non-Antioxidant Feed on the occurrence of nasopharyngeal dysplasia. Testing of the antioxidant activity in feed was carried out using the DPPH assay. There were two groups of experimental animals including the treatment group (fed with Non-Antioxidant Feed) and the control group (fed with SB 11). All animals in each group were induced with 40 ppm formaldehyde by inhalation for 8 weeks and then euthanized using chloroform inhalation for nasopharyngeal tissue extraction. The results of the histopathological examination of the two groups were then statistically tested using the Mann-Whitney U test and obtained a value of P<0.05 (P=0.006), which means that there are effect of feeding Non-Antioxidants Feed on the degree of dysplasia in formaldehyde-induced wistar rats. The results can be associated with the ingredients contained in the feed given, differences in genetic polymorphisms of each subjects, and effect of body weight variations of the rats caused by randomization.